Methyl 2-(5,5-dimethyl-1,3,2-dioxa-borinan-2-yl)-4-nitro-benzoate - Jenkinson, S; Thompson, A; Simone, M (2012)
The six-membered boronate ester ring of the title compound, C13H16BNO6, adopts an envelope conformation with the C atom bearing the dimethyl substituents at the flap. The O-B-C-C torsion angles between the boronate group and the benzene ring are 72.5 (2) and 81.0 (2)°. The 4-nitro-benzoate unit adopts a slightly twisted conformation, with dihedral angles between the benzene ring and the nitrate and methyl ester groups of 17.5 (2) and 14.4 (3)°, respectively. In the crystal, inversion-related pairs of mol-ecules show weak π-π stacking inter-actions [centroid-centroid distance = 4.0585 (9) Å and inter-planar spacing = 3.6254 (7) Å].